Proactive Personality in Agile Teams: Insights from a Systematic Review of the Literature - Kuncoro, Aris Wahyu; Susita, Dewi; Swaramarinda, Darma Rika (Program Studi S3 Ilmu Manajemen, 2024)
This study investigates the relationship between Agile methodology and proactive personality in a professional context using a Systematic Literature Review (SLR) approach. Agile, known for its emphasis on flexibility, collaboration, and continuous iteration, provides an environment conducive to developing proactive behaviors. Individuals with a proactive personality, characterized by initiative, problem-solving, and innovation, significantly contribute to team success in Agile environments. The findings highlight a strong synergy between Agile practices and proactive individuals, where proactive team members facilitate quicker decision-making, innovation, and adaptability to change. However, teams with members who exhibit low levels of proactivity may struggle with collaboration and decision-making. The study offers both theoretical insights and practical implications for organizations, emphasizing the need to develop a proactive culture within Agile teams through recruitment, training, and leadership. By fostering proactive behavior, organizations can optimize the potential of Agile methodologies, enhancing overall team performance and project outcomes.